Primer Design and Annealing Temperature Optimization for Catalase (CAT) Gene Amplification in Rice (Oryza sativa L.) - Yulita, Nelfi; Violita; Achyar, Afifatul; Putri, Dwi Hilda (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Catalase (CAT) is an antioxidant enzyme that plays an important role in plant growht and defense against abiotic stress, one of which is rice (Oryza sativa). When plants are under abiotic stress conditions, the CAT gene will be regulated and expressed as a form of defense response to stress. To determine the expression of this CAT gene, optimal primers and annealing temperatures are needed to spesifically amplify the CAT gene. This study aims to design primers and determine the optimal annealing temperatures to amplify the CAT gene. Primers are designed using the tools pick primer, primer BLAST and geneious prime. Primers are designed in silico and must meet the ideal primer criteria because they will be used in vitro. Optimization of the annealing temperature was carried out using a PCR temperature gradient. The results of this study obtained a pair of primers, namely forward primer 5’-ATAAGTAGGGCGGTGTGTGG-3’ with a primer length of 20 bp, and reverse primer 5’-GCGAGTTGTTGTTGTTCCATAC-3’ with a primer length 22 bp. This primer pair produces a 185 bp amplicon in the Oryza sativa CAT gene. The optimum annealing temperature for this primer pair is 60ºC.